Leading Coherently : Reflections from Leaders Around the World. - Stanford-Blair, Professor Nancy (SAGE Publications, 2005)
Leading Coherently draws insight from 36 exemplary leaders to describe a natural and potent relationship between leadership formation, performance, and sustainability. Through sharing their leadership stories, leaders from across the globe reveal prominent themes about how leaders are formed to the role of influencing others toward the achievement of goals. Leaders also reveal how leaders perform such influence on others, and how leaders sustain themselves and their leadership influence over time and adversity.